Improving CS Performance by Developing Spatial Skills. - Parkinson, Jack; Margulieux, Lauren (Communications of the ACM, 2025)
The article focuses on enhancing computer science (CS) performance through the development of spatial skills. It examines the link between spatial skills and success in CS education, suggesting that spatial reasoning is crucial for understanding and solving CS problems. It emphasizes the value of incorporating spatial skills training into CS education, as it can enhance cognitive abilities. Topics of discussion include STEM education, human information processing, and memory.